Reactive oxygen species modulator 1 expression predicts lymph node metastasis and survival in early-stage non-small cell lung cancer - Kim, Taehee (PLoS One, 2020)
Reactive oxygen species modulator 1 (romo1) causes cell hyperplasia and promotes cancer cell invasion. Based recent studies, the overexpression of romo1 is associated with lymphatic metastasis and poor prognosis in lung cancer. We aimed to evaluate associations between romo1 expression and lymph node metastasis in non-small cell lung cancer (NSCLC). Clinical data and pathological results were retrospectively reviewed for 98 subjects diagnosed with NSCLC and who underwent surgical biopsy between 1994 and 2009. A total 98 tumor specimens were analyzed. The romo1 H score was correlated with stage and was significantly higher in subjects with lymph node metastasis than in those without metastasis (173 vs 116; P < 0.05). The area (%) of grade 1 expression was significantly smaller (19.5 vs 37.0; P = 0.005) and the area of grade 3 expression was significantly larger (27.9 vs 6.00; P < 0.001) in subjects with lymph node metastasis than in those without metastasis. In stage I patients, disease free survival (DFS) (191 ± 18.8 vs. 75.6 ± 22.4 months, P = 0.004) was significantly longer in the low romo1 group than in the high romo1 group. A multivariate analysis showed a significant association between high romo1 expression and poor DFS (hazard ratio 5.59, 95 confidence interval, 1.54–20.3, P = 0.009). These findings support the prognostic value of romo1 in NSCLC, especially in stage I.